Ossifying Fibroma in the Rostral Maxilla of Canis lupus familiaris - Silva, Stefanie Tenille Santana da; Aryadne Auana Costa; Amanda Cardoso dos Santos; Letícia Cristina Ribeiro; Léslie Maria Domingues; Danilo Maciel Duarte; Lessa Abdalla, Samira (Universidade Federal do Rio Grande do Sul, 2024)
Background: Ossifying fibroma (OF) is considered a rare occurrence in dogs and presents as a benign neoformation, with a low invasiveness, slow and progressive growth, smooth, firm, globose and pedunculated appearance, originating from cells of the periodontal ligament, its prominence is notable due to the presence of bone formation within the tumor mass. Diagnosis is made by histopathology and intraoral radiography. The recommended treatment is excision of this bone formation, with a good prognosis if removed completely. The aim of this paper was presents a literature review regarding the disease ossifying fibroma, together with a case study describing the diagnosis in Canis lupus familiaris. Case: An approximately 8-year-old mixed-breed castrated male dog, weighing 7.3 kg, was treated at the Veterinary Complex of the Centro Universitário Nossa Senhora do Patrocínio (CEUNSP), in Salto city, São Paulo state, Brazil. The patient had a firm, pigmented globose enlargement of the rostral maxilla. The treatment was carried out using the surgical technique of partial rostral maxillectomy under general inhalation anesthesia, performing assertive excision of the entire tumor region and its safety margin, with diagnosis made by macroscopic observation and histopathological examination associated with intraoral radiography, with a good prognosis according to our data which corroborate the literature, with the patient being monitored and no showing signs of local recurrence. Discussion: The importance of complementary diagnostic tests, such as histopathological and radiographic exams, in the routine of veterinary dentistry is mandatory in order to establish the diagnosis and therapeutic monitoring of Ossifying Fibroma (OF) and in order to discard differential diagnosis like to the fibrous dysplasia, which has similar histopathological findings but can be differentiated through radiographic imaging, which shows the presence of intratumoral bone formation. In the present report, in agreement with the majority of cases ...